Towards an asymmetric β-selective addition of azlactones to allenoates - Nasiri, Behzad; Pasdar, Ghaffar; Zebrowski, Paul; Röser, Katharina; Naderer, David; Waser, Mario (Beilstein Journal of Organic Chemistry, 2024)
We herein report the asymmetric organocatalytic addition of azlactones to allenoates. Upon using chiral quaternary ammonium salt catalysts, i.e., Maruoka’s binaphthyl-based spirocyclic ammonium salts, the addition of various azlactones to allenoates proceeds in a β-selective manner with moderate levels of enantioselectivities (up to 83:17 er). Furthermore, the obtained products can be successfully engaged in nucleophilic ring opening reactions, thus giving highly functionalized α-amino acid derivatives.
Keywords: allenoates; amino acids; azlactones; organocatalysis; quaternary ammonium salt catalysis